Effect of extrusion processing deformation and heat treating on the plastic flow, microstructure, and mechanical behavior of an aluminum alloy - Fragomeni, James M.; Pochampally, Sarita (Computer Assisted Methods in Engineering and Science; Vol 11 No 1 (2004), 2023)
The extrusion temperature, extrusion ratio and ram speeds were varied and finite element simulations of the extrusion process were conducted to determine the effect of these extrusion parameters on temperature transients, strain rate, and metal flow uniformity for the high temperature plastic deformation of an aluminum-lithium alloy billet. The finite element simulations were important in determining temperature transients, metal flow patterns, and the distributions of strain and strain rate during the extrusion process. The contours showed that the strain, strain rate and metal flow were not uniform but varied as the billet was extruded; this might be due to the non-uniform distribution of temperature during the extrusion of the billet. The microstructure of the aluminum-lithium alloy was computer simulated and correlated to the processing parameters and flow stress based on the heat treating times and temperatures. The extrusion processing variables were correlated to the Zener-Hollomon parameter temperature compensated strain rates. Extrusion temperature and extrusion ratio were found to have very little effect on the strength or ductility. The as-extruded section geometry was found to have the largest effect on the strength and ductility.